2020
DOI: 10.3389/fenrg.2020.604005
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Regulation for Transfer of Pollution-Intensive Industries: Evidence From Chinese Provinces

Abstract: How environmental regulations affect the transfer of pollution-intensive industries is the core issue of balanced regional development and pollution reduction in China. This paper analyses the theoretical mechanism of the impact of environmental regulation on industrial transfer based on the distinction between formal environmental regulation and informal environmental regulation. To this aim, the paper selects panel data of 30 provinces in China from 2008 to 2018 and uses the fixed effect econometric model to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Furthermore, the correlation is a positive one, meaning as electrification rate increases, renewables consumption of total energy consumption increases (Sun et al, 2020) and (Li et al, 2020).…”
Section: Regional Heterogeneity Effects and Mechanismsmentioning
confidence: 99%
“…Furthermore, the correlation is a positive one, meaning as electrification rate increases, renewables consumption of total energy consumption increases (Sun et al, 2020) and (Li et al, 2020).…”
Section: Regional Heterogeneity Effects and Mechanismsmentioning
confidence: 99%
“…First, prior studies found that environmental regulation can improve corporate environmental performance and affect the equity incentive mechanism of enterprises [ 43 , 44 ]. Thus, referring to Li et al (2020) [ 44 ], we used the proportion of regional pollution control investment in regional GDP to measure environmental regulation ( ER ) and added ER as a control variable to Equation (1).…”
Section: Empirical Results and Analysismentioning
confidence: 99%
“…First, prior studies found that environmental regulation can improve corporate environmental performance and affect the equity incentive mechanism of enterprises [ 43 , 44 ]. Thus, referring to Li et al (2020) [ 44 ], we used the proportion of regional pollution control investment in regional GDP to measure environmental regulation ( ER ) and added ER as a control variable to Equation (1). Second, because equity incentive plans may also influence corporate sustainability practices and environmental performance [ 45 ], we further controlled the dummy variable of whether the corporate implements equity incentive plans ( EIPs ) in Equation (1).…”
Section: Empirical Results and Analysismentioning
confidence: 99%
“…Liu et al (2017) also found that stricter wastewater discharge standards reduced the labor demand and production scales of enterprises. Secondly, the installation of abatement equipment is widely used by many firms to reduce pollutant emissions (Becker, 2011;Li et al, 2020). Thirdly, the "Porter Hypothesis" insists that appropriate environmental regulation will stimulate enterprises to carry out technological innovation and produce innovation compensation effect.…”
Section: Impact Mechanism Of the Environmental Target Responsibilitymentioning
confidence: 99%